Extraction and evaluation of citrus reticulate blanco peel essential oil as a potential anti-acne agent in a face cream - Castillo, Mary Vanessa D.; Escober, Alynna Flor A.
Acne vulgaris is a multifactorial inflammatory skin condition that affects approximately 85 percent of 12 to 24-year-olds in the Philippines and has a significant impact on the social, psychological, and emotional functioning of those affected. Natural skin occupants Cutibacterium acnes and Staphylococcus epidermidis are frequently isolated from acne lesions. These bacteria are believed to contribute to the inflammation of acne and are often the target for acne therapy. The essential oil from Citrus reticulata Blanco peel has been reported to contain several bioactive compounds such as limonene and has been demonstrated to have activity against C. acnes. As such, the objectives of this study were to quantify d-limonene in the Citrus reticulata Blanco peel essential, to formulate a face cream containing the C. reticulata Blanco peel essential oil, to evaluate the physicochemical properties of the face cream, and to evaluate the antibacterial activity of the extracted essential oil and the formulated face cream against C. acnes and S. epidermidis. Fresh peels of C. reticulata Blanco obtained from Binogawan, Kasibu, Nueva Vizcaya underwent hydrodistillation to extract the peel essential oil which was then subjected to GC-MS analysis for characterization and quantification of d-limonene content. Preliminary analysis of microbial activity of the essential oil was performed using turbidimetric method. A face cream was formulated containing the C. reticulata Blanco peel essential oil, which was then subjected to tests to evaluate its antimicrobial, physicochemical, and organoleptic properties. From 6.7S kilograms of fresh fruit peels, 11.37 ml of essential oil was obtained, corresponding to 1.68 mL of essential oil per kilogram of fresh peel. The essential oil contains 69 compounds, with d-limonene accounting for 72.42% of its chemical constituents. The measured decrease in turbidity of bacterial inoculum containing 5 and 20 uL of essential oil has shown potential activity against C. acnes. The formulated cream containing the essential oil exhibited desired organoleptic and physicochemical properties but was found to be unstable when stored at 40°C. The current findings show evidence that Philippine-grown Citrus reticulata Blanco peel essential oil contains relatively high amounts of d-limonene and has the potential to be further studied for its applicability in acne therapy as a face cream. Disk diffusion assay to confirm the activity of the essential oil and the formulated cream against C. acnes and S. epidermidis are still underway.